Synthesis of structurally diverse 3,4-dihydropyrimidin-2(1H)-ones via sequential Biginelli and Passerini reactions - Boukis, Andreas C.; Monney, Baptiste; Meier, Michael A. R. (Beilstein Journal of Organic Chemistry, 2017)
The Biginelli reaction was combined with the Passerini reaction for the first time in a sequential multicomponent tandem reaction approach. After evaluation of all possible linker components and a suitable solvent system, highly functionalized dihydropyrimidone–α-acyloxycarboxamide compounds were obtained in good to excellent yields. In a first reaction step, different 3,4-dihydropyrimidin-2(1H)-one acids were synthesized, isolated and fully characterized. These products were subsequently used in a Passerini reaction utilizing a dichloromethane/dimethyl sulfoxide solvent mixture. By variation of the components in both multicomponent reactions, a large number of structurally diverse compounds could be synthesized. In addition, a one-pot Biginelli–Passerini tandem reaction was demonstrated. All products were carefully characterized via 1D and 2D NMR as well as IR and HRMS.
Keywords: Biginelli reaction; molecular diversity; multicomponent reactions; Passerini reaction; tandem reactions

(untitled) - Touré, B. B.; Hall, D. G. (Chem. Rev., 2009)

(untitled) - D’Souza, D. M.; Müller, T. J. J. (Chem. Soc. Rev., 2007)

(untitled) - Dömling, A.; Ugi, I. (Angew. Chem., Int. Ed., 2000)

(untitled) - Gu, Y. (Green Chem., 2012)

(untitled) - Ganem, B. (Acc. Chem. Res., 2009)

(untitled) - Boukis, A. C.; Llevot, A.; Meier, M. A. R. (Macromol. Rapid Commun., 2016)

(untitled) - Xue, H.; Zhao, Y.; Wu, H.; Wang, Z.; Yang, B.; Wei, Y.; Wang, Z.; Tao, L. (J. Am. Chem. Soc., 2016)

(untitled) - Hu, R.; Li, W.; Tang, B. Z. (Macromol. Chem. Phys., 2016)

Multicomponent reactions - Zhu, J.; Bienaymé, H. (John Wiley & Sons, 2006)

(untitled) - Biginelli, P. (Ber. Dtsch. Chem. Ges., 1891)

(untitled) - Tron, G. C.; Minassi, A.; Appendino, G. (Eur. J. Org. Chem., 2011)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Ajani, O. O.; Isaac, J. T.; Owoeye, T. F.; Akinsiku, A. A. (Int. J. Biol. Chem., 2015)

(untitled) - Selvam, T. P.; James, C. R.; Dniandev, P. V.; Valzita, S. K. (Res. Pharm., 2012)

(untitled) - Sepehri, S.; Sanchez, H. P.; Fassihi, A. (J. Pharm. Pharm. Sci., 2015)

(untitled) - Kappe, C. O. (J. Org. Chem., 1997)

(untitled) - Puripat, M.; Ramozzi, R.; Hatanaka, M.; Parasuk, W.; Parasuk, V.; Morokuma, K. (J. Org. Chem., 2015)

(untitled) - Alvim, H. G. O.; da Silva Júnior, E. N.; Neto, B. A. D. (RSC Adv., 2014)

(untitled) - Folkers, K.; Johnson, T. B. (J. Am. Chem. Soc., 1933)

(untitled) - Sweet, F.; Fissekis, J. D. (J. Am. Chem. Soc., 1973)

(untitled) - Passerini, M.; Simone, L. (Gazz. Chim. Ital., 1921)

(untitled) - Nicolaou, K. C.; Edmonds, D. J.; Bulger, P. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Tietze, L. F. (Chem. Rev., 1996)

(untitled) - Parsons, P. J.; Penkett, C. S.; Shell, A. J. (Chem. Rev., 1996)

(untitled) - Behr, A.; Vorholt, A. J.; Ostrowski, K. A.; Seidensticker, T. (Green Chem., 2014)

(untitled) - Zhou, J. (Chem. – Asian J., 2010)

(untitled) - Batey, R. A. (J. Am. Chem. Soc., 2007)

(untitled) - Brauch, S.; van Berkel, S. S.; Westermann, B. (Chem. Soc. Rev., 2013)

(untitled) - Cioc, R. C.; Ruijter, E.; Orru, R. V. A. (Green Chem., 2014)

(untitled) - Portlock, D. E.; Ostaszewski, R.; Naskar, D.; West, L. (Tetrahedron Lett., 2003)

(untitled) - Portlock, D. E.; Naskar, D.; West, L.; Ostaszewski, R.; Chen, J. J. (Tetrahedron Lett., 2003)

(untitled) - Al-Tel, T. H.; Al-Qawasmeh, R. A.; Voelter, W. (Eur. J. Org. Chem., 2010)

(untitled) - Elders, N.; van der Born, D.; Hendrickx, L. J. D.; Timmer, B. J. J.; Krause, A.; Janssen, E.; de Kanter, F. J. J.; Ruijter, E.; Orru, R. V. A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Brauch, S.; Gabriel, L.; Westermann, B. (Chem. Commun., 2010)

(untitled) - Fewell, S. W.; Smith, C. M.; Lyon, M. A.; Dumitrescu, T. P.; Wipf, P.; Day, B. W.; Brodsky, J. L. (J. Biol. Chem., 2004)

(untitled) - Werner, S.; Turner, D. M.; Lyon, M. A.; Huryn, D. M.; Wipf, P. (Synlett, 2006)

(untitled) - Wu, H.; Fu, C.; Zhao, Y.; Yang, B.; Wei, Y.; Wang, Z.; Tao, L. (ACS Macro Lett., 2015)

(untitled) - Sung, K.; Chen, C.-C. (Tetrahedron Lett., 2001)

(untitled) - Solleder, S. C.; Zengel, D.; Wetzel, K. S.; Meier, M. A. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Lutz, J.-F.; Lehn, J.-M.; Meijer, E. W.; Matyjaszewski, K. (Nat. Rev. Mater., 2016)

(untitled) - Feng, X.; Ding, X.; Jiang, D. (Chem. Soc. Rev., 2012)

(untitled) - Muller, T.; Bräse, S. (RSC Adv., 2014)